2008
DOI: 10.1016/j.asr.2007.10.016
|View full text |Cite
|
Sign up to set email alerts
|

Spaceflight results in increase of thick filament but not thin filament proteins in the paramyosin mutant of Caenorhabditis elegans

Abstract: We have investigated the effect of microgravity during spaceflight on body-wall muscle fiber size and muscle proteins in the paramyosin mutant of Caenorhabditis elegans.Both mutant and wild-type strains were subjected to 10 days of microgravity during spaceflight and compared to ground control groups. No significant change in muscle fiber size or quantity of the protein was observed in wild-type worms; where as atrophy of body-wall muscle and an increase in thick filament proteins were observed in the paramyos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 33 publications
1
6
0
Order By: Relevance
“…Since we are dealing with an entire organism and not with a single cell line, our results are in line with the observation reported above. Moreover, our data are in perfect agreement with the observation of Adachi et al (2008) who did not detect significant changes of actin and tropomyosin amount in Caenorhabditis elegans upon space flight. Accordingly, besides actin, also the amount of α‐tropomyosin (spot 58), another important component of thin filaments, does not change in X. laevis in RPM (Figure 2).…”
Section: Resultssupporting
confidence: 92%
“…Since we are dealing with an entire organism and not with a single cell line, our results are in line with the observation reported above. Moreover, our data are in perfect agreement with the observation of Adachi et al (2008) who did not detect significant changes of actin and tropomyosin amount in Caenorhabditis elegans upon space flight. Accordingly, besides actin, also the amount of α‐tropomyosin (spot 58), another important component of thin filaments, does not change in X. laevis in RPM (Figure 2).…”
Section: Resultssupporting
confidence: 92%
“…Phalloidin and anti-paramyosin staining of post-flight animals revealed no gross morphologic changes, including no change in the width of the fibers. While these results indicate a lack of spaceflight induced “atrophy” of the fibers, the animals used for histologic analysis did not show the same depression in paramyosin and myosin heavy chain B (Adachi et al, 2008) as the animals that had a post-flight movement defect (Higashibata et al, 2006), thus reinforcing the idea that there are individual specific differences that underlie spaceflight-induced alterations in muscle. If this is true than C. elegans would appear to mirror the situation in human beings where there appears to be great variability in muscle atrophy in response to spaceflight (Fitts et al, 2001, Adams et al, 2003).…”
Section: Muscle Adaptation In Spaceflightmentioning
confidence: 83%
“…STS-107 showed C. elegans could survive a relatively unprotected atmospheric reentry and began the validation of the use of a chemically defined liquid growth medium in spaceflight experiments (Szewczyk et al, 2005). ICE-FIRST: i) validated use of the chemically defined medium in spaceflight experiments (Szewczyk et al, 2008); ii) confirmed a lack of developmental abnormalities (Szewczyk et al, 2008); iii) verified that apoptosis occurs normally in spaceflight (Higashitani et al, 2005); iv) showed that C. elegans display many of the same changes in muscle gene expression as mammals (Adachi et al, 2008, Higashibata et al, 2006, Selch et al, 2008); v) determined that spaceflight partially rescued a muscular defect in a paramyosin mutant strain (Adachi et al, 2008) and intramuscular protein aggregation (Honda et al, 2012); vi) suggested that altered metabolic (Insulin-like and/or TGF-beta) signaling pathways were responsible for the in-flight changes in gene expression (Selch et al, 2008); vii) determined that some genes down-regulated during spaceflight are linked to longevity processes in C. elegans (Honda et al, 2012); and viii) confirmed that the eTI balancer system can easily capture increased mutagenic effects of spaceflight (Zhao et al, 2006) and postulated that the eTI system could be used as a “biological dosimeter” to measure the long-term mutagenic effects of spaceflight (Zhao et al, 2005). Shijian-8 explored some of the potential molecular mechanisms behind spaceflight muscular atrophy (Wang et al, 2008).…”
Section: Introductionmentioning
confidence: 77%